Getting an Heir Adoption and the Construction of Kinship in Late Imperial China - Waltner, Ann (University of Hawai'i Press, 1990)
The need for heirs in any traditional society is a compelling one. In traditional China, where inheritance and notions of filiality depended on the production of progeny, the need was nearly absolute. As Ann Waltner makes clear in this broadly researched study of adoption in the late Ming and early Ch'ing periods, the getting of an heir was a complex, even paradoxical undertaking. Although adoption involving persons of the same surname was the only arrangement ritually and legally sanctioned in Chinese society, adoption of persons of a different surname was a relatively common practice. Using medical and ritual texts, legal codes, local gazetteers, biography, and fiction, Waltner examines the multiple dimensions of the practice of adoption and identifies not only the dominant ideology prohibiting adoption across surname lines, but also a parallel discourse justifying the practice.